Corrosion inhibition and adsorption mechanism of Morus nigra on mild steel in acidic medium: A sustainable and green approach. Issue 4 (6th June 2022) - Kumar, Harish; Sharma, Shalu; Kumari, Rajni
Abstract: Morus nigra (Mulberry leaves) was tested as a green inhibitor for mild steel (MS) in 0.5 M HCl by theoretical, surface study, and experimental techniques. The impedance, polarization, microscopy, Langmuir, and DFT (computational) techniques were used for the adsorption and corrosion inhibition study. The experimental and theoretical study supports each other results. Adsorption parameters were observed by Langmuir, Gaussian09W (DFT), and BIOVIA Materials Studio softwares. The surface study was carried out by metallurgical microscopy technique. The theoretical study includes chemical potential, electron‐donating power, chemical hardness, HOMO, LUMO, metal inhibitor interaction energy, adsorption energy, etc. UV‐visible, NMR, and FTIR studies show that aspartic acid is the major constituent present in the mulberry leaves extract. A 91.62% corrosion protection was provided by the Morus nigra at 1000 ppm. Polarization study proved mixed inhibition. The green inhibitor follows both physical and chemical modes of adsorption. The biochemical and chemical oxygen demand of unused acid left after the gravimetric study was found in an acceptable range. Abstract :